The importance of healthy eating habits in old age (Research, Society and Development, 2021)
The overall objective of the study is to highlight the importance of healthy eating habits among malnourished elderly. It is mentioned that the specific objectives of the study are:  To understand the relationship between the physiological changes that occur in aging and the nutritional needs of the elderly. Raise aspects of the etiology of malnutrition in the elderly; and highlight the importance of nutritional follow-up in the elderly population in the development of healthy habits. This research is a review of the integrative. The database used were: PubMed, Virtual Health Library (VHL) and SciELO and other nutrition journals. The strategy elaborated for inclusion in this research were: a study published in journals indexed in English, Spanish and Portuguese, available in full, free of charge, addressing the proposed theme, which were duly published in the period 2015 to 2021. The strategy elaborated for exclusion were studies published before 2015, which were not available in full, and were unrelated to the proposed theme. Thus, 367 studies were found, of this total 85 were selected, but only 37 studies were analyzed in this article. It is concluded that there are different risk factors for malnutrition in the elderly, this nutritional status is a risk factor for the development of diseases and can lead to death. Therefore, family members should act to avoid this situation, but when developed it is relevant that the elderly be accompanied by the nutritionist, because the professional can analyze the clinical picture and develop appropriate dietary strategies for patients.